The Effect of Traditional Game-Based Physical Activity on Cardiovascular Endurance of Elementary School Students - Novia Nurul Mustami; Rahmat Permana; Anggia Suci Pratiwi (BASICA, 2026)
This research aimed to examine the effect of traditional game-based physical activity on cardiovascular endurance in Physical Education, Sports, and Health (PJOK) learning among fifth-grade elementary school students. The activities were implemented through traditional games (boy-boyan, gobak sodor, lari balok, and ucing-ucingan) designed to involve dynamic movements in a structured and progressive manner. This research employed a quasi-experimental method with a nonequivalent control group design. The participants consisted of 52 fifth-grade students at SD Negeri Sambongpari, divided into an experimental group (n = 26) and a control group (n = 26). The experimental group received traditional game-based instruction, while the control group followed conventional PJOK instruction. Data were collected using the Foster Test to measure cardiovascular endurance and were analyzed using descriptive statistics and the Mann–Whitney U test at a significance level of 0.05. The results indicated differences between pretest and posttest scores in both groups, with a greater mean difference in the experimental group improved from 4.23 to 9.15, whereas the control group increased from 4.38 to 5.73. Statistical analysis revealed a significant difference between the posttest results of the two groups (Z = -3.777; p < 0.001). These findings indicate that traditional game-based activities can serve as an effective pedagogical strategy in physical education to improve students’ cardiovascular fitness.